Inovasi Pelayanan Program Siap Melayani Masyarakat Malam Hari (SIMMAMAH) di Kecamatan Taman Sidoarjo (Soetomo Administrasi Publik, 2025)
Over time, community needs are also increasing, one of which is the need for administrative services. Many people who work during the day have problems related to population administration where they cannot take care of it because they are working, and usually the operating hours and service schedules are not in accordance with working hours. Taman Subdistrict has launched an innovation in optimizing administrative services through the SIMMAMAH Program. The purpose of this study was to determine and analyze how the SIMMAMAH public service innovation program can be accepted by the Taman community. This research focuses on the five attributes of Rogers' service innovation, using a qualitative descriptive research method. The data collection technique itself uses interview techniques, observation to obtain qualitative data, and documentation retrieval techniques used to obtain a direct picture of the field. The results of the study show that the Ready to Serve the community at Night (SIMMAMAH) service innovation program is based on five attributes which are the most important characteristics of innovation in explaining the level of adoption. The five attributes are: relative advantage, compatibility, complexity, triability, observability which have been well implemented by the Taman Subdistrict through the SIMMAMAH program